STRATEGI PENGEMBANGAN SUMBER DAYA MANUSIA MELALUI LITERASI DIGITAL DI MTs NURUL YASIN BUER SUMBAWA - Aifalesasunanda, Rizka; Citriadin, Yudin; Maujud, Fathul (ASCENT: Al-Bahjah Journal of Islamic Education Management, 2024)
The background of this research is the fact that many teachers still use poor resources, which has an impact on teacher quality. To improve human resources through the use of digital literacy to improve the quality of teachers in Mts Nurul Yasin Buer. The case study sites are MTs Nurul Yasin Buer. This research aims to analyze human resource development strategies. This research was conducted qualitatively with a case study approach. Observation, interview, and documentation study were used to collect data. The results show that teachers have not fully used digital literacy in the learning process although schools have used various strategies, such as providing technological infrastructure and improving teachers' abilities. In addition, schools still face a number of challenges; limited budgets, variations in teachers' capacity for digital literacy, and lack of parental participation. Schools should increase budgets and infrastructure, strengthen teachers' capabilities, balance the curriculum and involve parents more actively to address these issues.